Labor Resilience During the Climate Crisis: The Strategic Function of BPJS Ketenagakerjaan in the Informal Sector - Minkhaya Silviana Putri; Ardi Rifai (BPJS Ketenagakerjaan, 2026)
This study examines the strategic role of BPJS Ketenagakerjaan in strengthening labor resilience in the context of climate change, particularly among informal workers in Indonesia. The study employed a qualitative systematic literature review using a critical-interpretive synthesis approach to integrate national and international evidence on climate-induced labor risks, access to social protection, and institutional adaptability. The findings indicate that while BPJS Ketenagakerjaan has expanded its formal coverage, its capacity to address climate-related disruptions is limited by rigid regulations, fragmented governance, and a lack of climate risk integration. Informal and climate-sensitive workers remained the least protected, highlighting a gap between program design and actual climate-related risks. Comparative evidence from Bangladesh, Vietnam, and the Philippines shows that integrating climate risk analysis and adaptive benefit mechanisms can significantly enhance institutional responsiveness. The study finds that transforming BPJS Ketenagakerjaan into a climate-adaptive social protection institution requires integrating climate risk into policy frameworks, strengthening inter-agency coordination, and expanding coverage for informal workers. These reforms are crucial to ensuring equitable and climate-resilient employment protection in Indonesia's evolving labor landscape.